Respuesta :
Answer:
y+1=3(x+1)
Step-by-step explanation:
slope= (3-(-3))/(2-0) = 3
y=3x+b
-1=3(-1)+b
b=-2
y=3x-2
Convert to point slope form:
y+1=3(x+1)
Answer:
[tex]y=3x+2[/tex]
Step-by-step explanation:
Given : The given line passes through the points (0,-3) and (2,3).
To Find: What is the equation, in point-slope form, of the line that is parallel to the given line and passes through the point (-1,-1)?
Solution:
Points : (0,-3) and (2,3).
To find the equation of given points we will use two point slope form
Formula : [tex]y-y_1=m(x-x_1)[/tex] --A
Where m is the slope
[tex]m = \frac{y_2-y_1}{x_2-x_1}[/tex]
[tex](x_1,y_1)=(0,-3)[/tex]
[tex](x_2,y_2)=(2,3)[/tex]
So, [tex]m = \frac{3-(-3)}{2-0}[/tex]
[tex]m = \frac{6}{2}[/tex]
[tex]m = 3[/tex]
Now substitute the values in A
[tex]y+3=3(x-0)[/tex]
[tex]y+3=3x[/tex]
Two lines are said to be parallel when they have same slope
So, The line parallel to the given line will have slope =3
General form of equation of line = [tex]y=mx+c[/tex]
Substitute m = 3
So, parallel line : [tex]y=3x+c[/tex] ---B
Now this parallel lines passes through point (-1,-1)
So, substitute this point in B
[tex]-1=3(-1)+c[/tex]
[tex]-1=-3+c[/tex]
[tex]2=c[/tex]
Substitute value of c in B
So, Equation of parallel line = [tex]y=3x+2[/tex]
Hence the equation, in point-slope form, of the line that is parallel to the given line and passes through the point (-1,-1) is [tex]y=3x+2[/tex]